IMPLEMENTASI CLOUD COMPUTING DI BEBERAPA INSTANSI PEMERINTAHAN - Wildana, Faiq (Kementerian Komunikasi dan Informatika R.I., 2017)
AbstractAlong with the development of cloud computing technology, several government institution are ready to use cloud computing, even some have started implementing this technology. Currently cloud computing has just recently adapted in Indonesia. It is important to know the comparison and usage analysis of some instituitions that have been used. This study used a qualitative approach with interview instrument conducted for each instituition. Respondents who become the object of this research are LKPP, BIG, Balai IPTEK-net BPPT, and Ministry of Communications and Informatics. The four instituitions are selected because it is a central instituition that has been implemented cloud computing with a wide range of services. The method of analysis used is a comparative method which compares cloud computing services. Comparative analysis approach is issues and challenges of cloud computing. The study produces an overview of the application of cloud computing in government instituitions along with suggestions that should be done.AbstrakSeiring dengan perkembangan teknologi cloud computing, beberapa instansi pemerintahan sudah merencanakan pemanfaatan cloud computing, bahkan sudah ada yang mulai memanfaatkan teknologi ini. Sedangkan cloud computing belum lama ini baru mulai diadaptasi di Indonesia. Kiranya penting untuk mengetahui komparasi dan analisis pemakaian oleh beberapa instansi yang sudah menggunakan. Penelitian ini menggunakan pendekatan kualitatif dengan instrumen wawancara yang dilakukan kepada masing-masing instansi. Responden yang menjadi objek penelitian ini yaitu LKPP, BIG, Balai IPTEK-net BPPT, dan Kementerian Kominfo. Keempat instansi tersebut dipilih karena merupakan instansi pusat yang diketahui sudah menerapkan cloud computing dengan jangkauan layanan yang luas. Metode analisis yang digunakan adalah metode komparatif dimana membandingkan keempat objek penelitian terkait layanan cloud computing yang diberikan. Analisis komparasi menggunakan pendekatan isu dan tantangan cloud computing. Studi menghasilkan gambaran penerapan cloud computing di instansi pemerintahan beserta saran yang seharusnya dilakukan.